1908
DOI: 10.1017/s0021859600000654
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Studies of Egyptian Cotton

Abstract: The Khedivial Agricultural Society of Egypt recently voted a capital expenditure of £2000 towards the establishment of a Mendelian Experiment Station for the study of heredity in cotton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1917
1917
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Cotton was one of the first crop plants to which Mendelian principles of genetics were applied (Balls, 1906;Shoemaker, 1908). Cytogenetic analyses revealed that the cultivated species G. hirsutum and G. barbadense and several other New World allotetraploids contained 52 chromosome, whereas most other diploid species contained just 26 chromosomes.…”
Section: Cytogenetic Resources Of Cottonmentioning
confidence: 99%
“…Cotton was one of the first crop plants to which Mendelian principles of genetics were applied (Balls, 1906;Shoemaker, 1908). Cytogenetic analyses revealed that the cultivated species G. hirsutum and G. barbadense and several other New World allotetraploids contained 52 chromosome, whereas most other diploid species contained just 26 chromosomes.…”
Section: Cytogenetic Resources Of Cottonmentioning
confidence: 99%
“…Early 20 th century interdisciplinary-integrated cotton research in Egypt and USA: In this regard, it is noteworthy that about a century ago a major research program on improvement of the Egyptian long-staple cotton (Gossypium barbadense L.) was already established on the basis of a multidisciplinary approach (Balls, 1907(Balls, , 1915. Balls (1907) pioneered the application of the then rediscovered Mendelian genetics as well as in integrating crop physiological/agronomical research within the cotton breeding program at Giza Station, with several substations across the country to test cultivar adaptability to variations in atmospheric and edaphic factors (i.e., genotypic x environment interaction).…”
Section: An Overview Of the Role Of Physiological Research In Crop Immentioning
confidence: 99%
“…Balls (1907) pioneered the application of the then rediscovered Mendelian genetics as well as in integrating crop physiological/agronomical research within the cotton breeding program at Giza Station, with several substations across the country to test cultivar adaptability to variations in atmospheric and edaphic factors (i.e., genotypic x environment interaction). Balls (1915) discussed in great detail the growth of cotton (including studies on stomatal behavior in reaction to cultural practices and climate) as affected by the heavy clay soils, with moderate levels of salinity, in the Nile river delta.…”
Section: An Overview Of the Role Of Physiological Research In Crop Immentioning
confidence: 99%
“…$4-6 billion/year. Cotton was among the first species to which the Mendelian principles were applied (Balls, 1906) and has a long history of improvement through breeding, with sustained long-term yield gains of 7 -lO kg of lint/ha/year (Meredith and Bridge, 1984).…”
Section: E Malvaceae: Cotton (Gossrpium Spp)mentioning
confidence: 99%
“…Other traits such as nematode resistance (Yik and Birchfield, 1984) and unique natural products have been identified (Balls, 1906) in wild diploids. Efforts to introgress quantitative traits, such as fiber properties, have had limited success .…”
Section: Application Of Dna Markers To Cotton Improvementmentioning
confidence: 99%